2017
DOI: 10.1007/s00408-017-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Observational Study on the Association Between Serum Mannose-Binding Lectin Levels and Severe Outcome in Critically Ill Patients with Pandemic Influenza Type A (H1N1) Infection

Abstract: This study shows that baseline MBL > 1870 ng/ml is associated with higher mortality in ICU patients with severe A(H1N1)pdm09 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
0
19
1
Order By: Relevance
“…We also observed that mannan-binding lectin (MBL2), an innate immune lectin that binds several different glycans [e.g., Lewis structures (14,15), high mannose (16), yeast mannans (17), and fucose (15)], recognizes influenza virus-infected cells in a high mannose-dependent manner. MBL2 is also associated with the severity of influenza in mouse models (18) and more recently in clinical analysis (19). Together, our data argue that the high mannose motif is an influenza infection-associated molecular pattern on host cells that guides immune responses leading to the concomitant damage associated with influenza disease severity.…”
Section: Significancementioning
confidence: 52%
“…We also observed that mannan-binding lectin (MBL2), an innate immune lectin that binds several different glycans [e.g., Lewis structures (14,15), high mannose (16), yeast mannans (17), and fucose (15)], recognizes influenza virus-infected cells in a high mannose-dependent manner. MBL2 is also associated with the severity of influenza in mouse models (18) and more recently in clinical analysis (19). Together, our data argue that the high mannose motif is an influenza infection-associated molecular pattern on host cells that guides immune responses leading to the concomitant damage associated with influenza disease severity.…”
Section: Significancementioning
confidence: 52%
“…5a ) (11, 2931). Taken together, our work provides a new mechanism that could explain the observation that both UPR activation and MBL2 levels directly associate with severity of outcome from influenza infection (13, 18, 19).…”
Section: Resultsmentioning
confidence: 67%
“…Upon binding, MBL2 activates the complement cascade and corresponding inflammatory response (44). A recent study on critically ill patients infected with H1N1pdm09 virus showed a strong correlation between levels of MBL2 in the blood and patient death (19). In addition, schizophrenics and multiple sclerosis patients, both have high levels of MBL2 and unusually high death rates from influenza and pneumonia (4548).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complement inducing lectin MBL2, which binds this induced glycan epitope has been strongly associated with influenza severity. 20,21 We hypothesize that the induced high mannose may play a causative role in the damage observed from MBL2 levels in influenza.…”
Section: Introductionmentioning
confidence: 98%